Myocardial Infarction Pathogenesis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Myocardial infarction remains a leading cause of morbidity and mortality worldwide, yet gaps persist in understanding its multifactorial pathogenesis and optimal management strategies. While extensive research has explored the role of atherosclerosis and ischemic imbalance, the interplay of thrombotic mechanisms and metabolic disturbances requires further investigation. This study employs a qualitative review methodology, synthesizing existing literature on myocardial infarction classification, pathophysiology, and treatment approaches. The findings confirm that atherosclerosis-induced thrombosis is the predominant cause, with ischemic imbalance exacerbating myocardial damage through metabolic acidosis and impaired cardiac electrophysiology. Results emphasize the need for early risk assessment, advanced thrombolytic therapies, and personalized treatment strategies to mitigate infarct progression. These insights have significant clinical implications, advocating for enhanced diagnostic biomarkers, targeted pharmacological interventions, and preventive measures to reduce cardiovascular disease burden. Future research should focus on molecular mechanisms and precision medicine approaches to improve early detection, treatment efficacy, and long-term patient outcomes.